An exploratory research on the benefits of a web-based cognitive training programme for higher education students. - Weimann, Tanya (My University, 2015)
Prior research has revealed that benefits of cognitive training include greater ability to carry out daily activities in adults (Willis et al: 2006), reduced risks of being involved in a motor vehicle accident (Ball et al: 2010) and improvements in academic performance (Merzerich et al: 1996; Holmes et al: 2009). The study explores whether a web-based cognitive training programme supported any improvement on the cognitive skills of higher education students. The quantitative research study was conducted with the use of a survey questionnaire on a group of third-year Travel and Tourism Management students after participating in the brain training over a 4-week period. Results showed positive cognitive outcomes being perceived by the respondents in the areas of working memory, attention, speed of processing and problem-solving skills. Respondents found a positive general result in their daily activities, such as overall improvement in their visual attention. Respondents indicated a small improvement in their memory skills such as being able to remember the content of a lecture more accurately. The results of the study also show that respondents found an improvement in their concentration in the classroom, their ability to react faster to questions and their ability to work faster with less errors. Problem-solving skills such as being able to calculate figures mentally also showed an improvement. It is recommended that further exploration on the ability of the mind to change in all phases of the life-cycle be pursued and further attention be given to present such a programme to higher education students as an added value to their studies and daily activities.
Keywords: Cognitive training; Web-based training; Academic performance; Memory skills; Problem-solving skills